Rare earth metal element modified lithium ion battery composite material and preparation method thereof

By constructing rare earth metal element-modified spinel and nanoheterojunction particle layers on the surface of the positive electrode material of lithium-ion batteries, the problem of insufficient surface stability of the positive electrode material is solved, and the cycle stability and electrochemical performance of the battery are significantly improved.

CN119400831AActive Publication Date: 2025-02-07WUHAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411546006.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The surface stability of the layered positive electrode material of lithium-ion batteries is insufficient, resulting in interface side reactions, surface transition metal dissolution and irreversible phase change, affecting the cycling performance and stability of the battery.

Method used

Using rare earth metal elements to modify lithium-ion battery composite materials, the interface of spinel material rich in oxygen vacancies and island-like distribution of nanoheterojunction particles are achieved to achieve the dual effect of coating doping and improve the surface Structural stability.

Benefits of technology

It effectively alleviates the dissolution and irreversible phase change in the battery cycle, and improves the cycle stability and electrochemical properties of the cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400831A_ABST
    Figure CN119400831A_ABST
Patent Text Reader

Abstract

The invention relates to a rare earth metal element modified lithium ion battery composite material and a preparation method thereof, and the preparation method comprises the following steps: constructing nano heterojunction particles which are rich in oxygen vacancies, fully cover a spinel surface and are distributed in an island shape on the surface of an electrode material through an in-situ coating doping process; the spinel surface with the nanoscale thickness can provide a rapid ion diffusion channel, and the situation that large-area spinel is formed, and consequently the capacity is reduced is avoided; due to the structural stability of spinel under high pressure, the phase change of harmful rock salt can be inhibited; and meanwhile, due to the fact that the coherent nano heterojunction particles have a plurality of octahedral vacancies, the ion diffusion rate can be increased, electron conduction is facilitated, the good electron conduction is beneficial to formation of a CEI interface rich in LiF, transition metal is protected, and the cycle stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a rare earth metal element modified lithium ion battery composite material and a preparation method thereof. Background Art

[0002] Layered cathode materials for lithium-ion batteries have attracted much attention due to their higher theoretical capacity. Typical layered materials include lithium cobalt oxide (LCO), ternary (NCM), lithium-rich manganese-based oxide (LLO), etc. Due to the interaction between the electrolyte and the cathode material, surface side reactions are one of the important reasons for limiting and maintaining the cycle life. Interface side reactions will lead to an increase in residual alkali on the surface and cause gelation of the slurry, which will affect the consistency of electrode preparation and increase the polarization of the battery, thereby reducing its cycle performance and stability. Part of the high capacity provided by the high cut-off voltage comes from the redox reaction of oxygen, which will cause oxygen to overflow from the surface, thereby bringing about the problem of surface transition metal dissolution. Therefore, improving the surface stability of layered materials is of vital importance for the development of better cathode materials and promoting the development of next-generation lithium-ion batteries.

[0003] In order to achieve the surface stability of positive electrode materials, various surface modification strategies have been widely studied and applied, such as coating and surface reconstruction. However, the thickness of the coating layer is difficult to effectively control, and too thick a coating layer will lead to problems such as decreased capacity and poor rate performance. It has been reported that some metal oxides, such as ZrO2, Al2O3, MgO, etc., are coated on the surface of the material. However, most of them exist in an amorphous form. Although the surface structure can be stabilized, these metal oxides will increase impedance and have loose bonding with the bulk material, resulting in poor cycle stability. Surface reconstruction may cause uncontrollable damage to the surface crystal structure, thereby affecting the stability of the surface structure. Therefore, designing a stable interface is of great significance to achieving excellent cycle stability of layered positive electrode materials under harsh conditions.

[0004] Combining various modification strategies and developing new modification methods to improve the structural stability of positive electrode materials and thereby improve the electrochemical properties of the materials, such as cycle life, has become an important direction of current research. Summary of the invention

[0005] In view of the above technical problems, the purpose of the present invention is to provide an effective surface coating strategy to simultaneously construct a coating layer of surface spinel and surface nano-heterojunction particles, and the surface-modified positive electrode material has excellent cycle stability.

[0006] In order to achieve the above object, the present invention adopts the following technical solution: A rare earth metal element modified lithium ion battery composite material, characterized in that the composite material has a core-shell structure, the core is a lithium ion battery positive electrode material, the shell is a spinel material interface rich in oxygen vacancies coated on the surface of the lithium ion battery positive electrode material, the spinel material rich in oxygen vacancies fully covers the surface of the lithium ion battery positive electrode material, and nano heterojunction particles are distributed in islands on the surface of the spinel material rich in oxygen vacancies, and both the spinel material rich in oxygen vacancies and the nano particle heterojunction structure contain rare earth metal elements.

[0007] Furthermore, the nano heterojunction particle material contains lithium, rare earth metal elements and oxygen.

[0008] Furthermore, the structural formula of the nano heterojunction particle material is Li x MO 2-y , M is one or more of lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), and yttrium (Y).

[0009] Furthermore, the thickness of the interface of the spinel material rich in oxygen vacancies is 1-5 nm, the nano heterojunction particles are hemispherical, trapezoidal or triangular pyramidal, and the average particle size of the nano heterojunction particles is 1-10 nm.

[0010] The present invention also provides a method for preparing a rare earth metal element modified lithium ion battery composite material, which is characterized by comprising the following steps: 1) Dissolve the positive electrode material, rare earth element source and metal ion adsorbent in ethanol according to a certain mass ratio, and stir in a water bath until the ethanol evaporates; 2) washing the product obtained above by centrifugation three times and drying; 3) The dried product is sintered at a certain temperature and naturally cooled to room temperature to obtain a surface-modified positive electrode material.

[0011] Furthermore, in the step 1), the rare earth element source used is one or more of the system metal sulfate, nitrate, acetate, chloride; the rare earth metal element is one or more of lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), yttrium (Y).

[0012] Furthermore, in the step 1), the metal ion adsorbent is one or more of urotropine, polyvinyl pyrrolidone, sodium alginate, and acrylonitrile; preferably urotropine. Furthermore, the mass ratio of the positive electrode material, the rare earth element source, and the metal ion adsorbent is 1: (0.01-0.015): (0.01-0.015).

[0013] Furthermore, in the step 1), the temperature of water bath stirring is 60-80°C; in the step 2), the solvent used for centrifugal washing is ethanol, and the drying temperature is 80-120°C; in the step 3), the sintering condition is 450-600°C, and the heat preservation is 2-6 h.

[0014] Furthermore, the present application also provides a use of the composite material as described in claims 1-4 or the composite material prepared by the method as described in claims 5-9 in a lithium ion battery.

[0015] The beneficial effects of the present invention are: Rare earth elements are introduced on the surface of lithium-ion positive electrode materials to achieve the dual effects of coating and doping, and a fully covered spinel surface rich in oxygen vacancies and nano-heterojunction particles distributed in islands are constructed on the surface of the positive electrode material. The spinel surface with nanometer-level thickness can provide a fast ion diffusion channel, and will not form a large area of ​​spinel to cause a decrease in capacity. Due to the structural stability of spinel under high pressure, harmful rock salt phase changes can be suppressed. The co-lattice nano-heterojunction particles also increase the ion diffusion rate and facilitate electronic conduction because they have many octahedral vacancies. Good electronic conduction is conducive to the formation of a CEI interface rich in LiF, protecting transition metals and improving cycle stability. The present invention obtains a positive electrode material having both nanoparticles and spinel surfaces, which can effectively alleviate the dissolution of transition metals and the occurrence of irreversible phase changes in battery cycles. When used as a lithium-ion positive electrode material, it has good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 (a) XRD spectrum and (c, d) SEM images of the lithium-rich material LLO@Ce after surface modification in Example 1 and the original lithium-rich material LLO.

[0017] Figure 2 (a) HAADF-STEM image, (b) EDS mapping image, and (c) atomic-resolution HAADF-STEM image of the lithium-rich material LLO@Ce after surface modification in Example 1.

[0018] Figure 3 The electrochemical curves at 0.2 C and the cycle performance comparison diagram (c) of the modified lithium-rich material LLO@Ce (a) and the original lithium-rich material LLO (b) in Example 1 are shown.

[0019] Figure 4 This is a comparison chart of the cycle performance of the modified lithium-rich material LLO@Ce in Example 1 and the original lithium-rich material LLO at a 1 C rate.

[0020] Figure 5This is a performance comparison chart of the modified lithium-rich material LLO@Ce prepared in Example 1 and the original lithium-rich material LLO at different rates.

[0021] Figure 6 These are atomic-resolution HAADF-STEM images of the modified lithium-rich material LLO@Ce (a, b) and the original lithium-rich material LLO (c, d) prepared in Example 1 after 100 cycles.

[0022] Figure 7 TEM images and XPS spectra (c) of the modified lithium-rich material LLO@Ce (a) and the original lithium-rich material LLO (b) prepared in Example 1 after 100 cycles.

[0023] Figure 8 This is the TEM image of the modified lithium-rich material LLO@Ce and the original lithium-rich material LLO prepared in Example 1 after 100 cycles. DETAILED DESCRIPTION

[0024] In order to make the technical solutions and advantages of the present invention clearer, the present invention and its beneficial effects will be further described in detail below in combination with specific implementation methods and the accompanying drawings of the specification, but the implementation methods of the present invention are not limited thereto. In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully below in combination with the accompanying drawings of the specification and preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0025] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0026] Unless otherwise specified, all reagents and raw materials used in the present invention are commercially available products or products that can be prepared by known methods.

[0027] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0028] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0029] Embodiment 1: 1) Dissolve 2 g of lithium-rich manganese-based (LLO) cathode material, 0.03 g of Ce(NO3)3·6H2O, and 0.03 g of metal ion adsorbent HMTA in ethanol and stir in a 60 °C water bath until the ethanol evaporates; 2) washing the product obtained above by centrifugation three times and drying; 3) The dried product is sintered at 450°C to obtain a surface-modified positive electrode material.

[0030] Embodiment 2: 1) Take 0.03 g La(NO3)3·6H2O, 0.03 g HMTA and 2 g of cobalt-free lithium-rich material powder (LRNM) prepared by coprecipitation-solid phase method and dissolve them in ethanol solution, and stir in a water bath at 60 °C until the ethanol evaporates. 2) The above product was washed by centrifugation for 3 times and dried at 80 °C.

[0031] 3) The product was placed in a muffle furnace at 500 °C for 3 h, cooled naturally to room temperature and taken out to complete the modification (LRNM@La).

[0032] Taking the cobalt-free lithium-rich material powder (LRNM) of the secondary particles of this embodiment as an example, surface modification (LRNM@La) was performed on it, confirming the effectiveness of this strategy for modifying the secondary particle positive electrode material samples.

[0033] Embodiment three: 1) Dissolve 0.03 g Ce(NO3)3·6H2O, 0.03 g sodium alginate and 2 g single crystal high nickel NCM811 powder in ethanol solution and stir in a water bath at 60 °C until the ethanol evaporates. 2) The above product was washed by centrifugation for 3 times and dried at 80 °C.

[0034] 3) Place the product in a muffle furnace at 450 °C for 2 h, cool it naturally to room temperature and take it out to complete the modification.

[0035] Embodiment 4: 1) Dissolve 0.03 g YbC6H9O6.xH2O, 0.03 g polyvinyl pyrrolidone and 2 g polycrystalline lithium cobalt oxide powder in ethanol solution and stir in a water bath at 60 °C until the ethanol evaporates. 2) The above product was washed by centrifugation for 3 times and dried at 80 °C.

[0036] 3) Place the product in a muffle furnace at 550 °C for 3 h, cool it naturally to room temperature and take it out to complete the modification.

[0037] The composite positive electrode material prepared above is then applied to the positive electrode sheet. The preparation method of the positive electrode sheet is as follows: the positive electrode material, polyvinylidene fluoride and SP-P are mixed and ball-milled at a mass ratio of 90:5:5 to obtain a positive electrode slurry, the positive electrode slurry is coated on the surface of the aluminum foil, after rolling, vacuum drying at 160°C overnight, and then cold pressing and die cutting to obtain the positive electrode sheet.

[0038] The obtained positive electrode sheet was applied to R2032 button battery for electrochemical performance test. The positive electrode sheet was used as the working electrode, the lithium foil was used as the counter electrode, the separator was GB-100R separator, and the non-aqueous electrolyte was used as the electrolyte (the specific preparation method was: ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L), and a lithium-ion button battery was made. Please refer to the existing preparation method, which will not be repeated here.

[0039] The obtained lithium-ion button battery was subjected to a constant temperature current charge and discharge test in a constant temperature box at about 25°C.

[0040] Figure 1 The (a) XRD spectrum and (c, d) SEM images of the lithium-rich material LLO@Ce after surface modification in Example 1 and the original lithium-rich material LLO. The XRD spectrum of LLO@Ce shows almost the same peaks as the unmodified powder, indicating that the surface reconstruction did not cause significant changes in the bulk crystal structure. TEM analysis shows that Li x CeO 2-y Evenly distributed on the LLO surface in the form of islands.

[0041] Figure 2 (a) HAADF-STEM image, (b) EDS mapping image, and (c) atomic-resolution HAADF-STEM image of the lithium-rich material LLO@Ce after surface modification in Example 1. x CeO 2-y Distributed on the LLO surface, and has a good spinel interface with LLO.

[0042] Figure 3This is a comparison chart of the cycle performance of the modified lithium-rich material LLO@Ce and the original lithium-rich material LLO at a rate of 0.2 C in Example 1. After 100 cycles, the capacity retention rate of LLO@Ce is 96.76%, and the voltage decay is suppressed.

[0043] Figure 4 This is a comparison chart of the cycle performance of the modified lithium-rich material LLO@Ce and the original lithium-rich material LLO at a rate of 1 C in Example 1. After 500 cycles, the capacity retention rate of LLO@Ce is 93.12%, showing an excellent capacity retention rate.

[0044] Figure 5 This is a comparison of the full battery cycle performance of the modified lithium-rich material LLO@Ce and the original lithium-rich material LLO at a rate of 1 C in Example 1, using commercial graphite as the negative electrode. After 400 cycles, the capacity retention rate of LLO@Ce is 90.52%, showing an excellent capacity retention rate.

[0045] Figure 6 The performance comparison diagram of the modified lithium-rich material LLO@Ce and the original lithium-rich material LLO prepared in Example 1 at different rates. As the rate increases, the gap between the capacity of LLO and LLO@Ce becomes larger and larger. At 5 C rate, LLO@Ce can obtain a capacity of 153.6 mAh g-1, while LLO has only 104.2 mAh g-1, which is only two-thirds of LLO@Ce. This shows that Li x CeO 2-y The nanoparticle and spinel interface provides good electrical conductivity.

[0046] Figure 7 This is a high-magnification HAADF-STEM image of the modified lithium-rich material LLO@Ce and the original lithium-rich material LLO after 100 cycles prepared in Example 1. x CeO 2-y There is no shedding and the material is tightly bonded, and the composite material structure is stable, while LLO has a large number of holes and cracks.

[0047] Figure 8 TEM images of the modified lithium-rich material LLO@Ce and the original lithium-rich material LLO after 100 cycles prepared in Example 1. Among them, LLO@Ce has a thin and uniform CEI film, and its composition is mainly inorganic LiF, which effectively alleviates the dissolution of transition metals.

[0048] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A rare earth metal element modified lithium ion battery composite material, characterized in that: The composite material has a core-shell structure, wherein the core is a lithium-ion battery positive electrode material, and the shell is an interface of a spinel material rich in oxygen vacancies coated on the surface of the lithium-ion battery positive electrode material. The spinel material rich in oxygen vacancies fully covers the surface of the lithium-ion battery positive electrode material, and nano-heterojunction particles are distributed in an island shape on the surface of the spinel material rich in oxygen vacancies. Both the spinel material rich in oxygen vacancies and the nano-particle heterostructure contain rare earth metal elements.

2. The rare earth metal element modified lithium ion battery composite material according to claim 1, characterized in that: The nano heterojunction particle material contains lithium, rare earth metal elements and oxygen.

3. The rare earth metal element modified lithium ion battery composite material according to claim 2, characterized in that: The structural formula of the nano heterojunction particle material is Li x MO 2-y , M is one or more of lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), and yttrium (Y).

4. According to the rare earth metal element modified lithium ion battery composite material of claim 1, the thickness of the spinel material interface rich in oxygen vacancies is 1-5nm, the nano heterojunction particles are hemispherical, trapezoidal or triangular pyramidal, and the average particle size of the nano heterojunction particles is 1-10nm.

5. A method for preparing a rare earth metal element modified lithium ion battery composite material according to any one of claims 1 to 4, characterized in that: The steps include: 1) Dissolve the positive electrode material, rare earth element source and metal ion adsorbent in ethanol according to a certain mass ratio, and stir in a water bath until the ethanol evaporates; 2) washing the product obtained above by centrifugation three times and drying; 3) The dried product is sintered at a certain temperature and naturally cooled to room temperature to obtain a surface-modified positive electrode material.

6. The preparation method according to claim 5, characterized in that: In the step 1), the rare earth element source used is one or more of rare earth metal sulfates, nitrates, acetates, and chlorides; the rare earth metal element is one or more of lanthanum (La), cerium (Ce), neodymium (Nd), samarium (Sm), and yttrium (Y).

7. The preparation method according to claim 5, characterized in that: In the step 1), the metal ion adsorbent is one or more of urotropine, polyvinyl pyrrolidone, sodium alginate, and acrylonitrile; preferably urotropine.

8. The preparation method according to claim 5, characterized in that: In the step 1), the mass ratio of the positive electrode material, the rare earth element source and the metal ion adsorbent is 1: (0.01-0.015): (0.01-0.015).

9. The preparation method according to claim 5, characterized in that: In the step 1), the temperature of water bath stirring is 60-80°C; in the step 2), the solvent used for centrifugal washing is ethanol, and the temperature of drying is 80-120°C; in the step 3), the sintering condition is 450-600°C, and the heat preservation is 2-6 hours.

10. Use of the composite material according to claims 1-4 or the composite material prepared by the method according to claims 5-9 in lithium ion batteries.

Citation Information

Patent Citations

  • NCM ternary cathode material with surface layer doping of Ce<3+> and surface layer coating of CeO2 and preparation method of the ternary cathode material

    CN109301207A

  • Linkage modified lithium-rich manganese-based positive electrode material and preparation method thereof

    CN111509224A

  • Positive electrode composite material, preparation method thereof and sodium ion battery

    CN117199322A

  • Surface ion exchange reaction-based coated spinel type positive electrode material and preparation method thereof

    CN117747818A